2022
DOI: 10.3390/ijerph19095412
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Horticultural Therapy on Sense of Coherence among Residents of Long-Term Care Facilities: A Quasi Experimental Design

Abstract: Promoting positive mental health is crucial for the elderly living in long-term care facilities (LTCFs). This study aims to examine the effectiveness of horticultural therapy on the level of sense of coherence (SOC) among older LTCF residents with relatively normal mental function. With convenient sampling, a total of 86 participants were recruited from 12 LTCFs in northeastern Taiwan. In the experimental group (n = 49), the mean (±standard deviation) score of SOC was 50.45 ± 6.07 at baseline and increased to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…The current study concluded that compassion-focused therapy is effective in improving feelings of coherence, as supported by other studies [22], [31], [39], which indicated that the sense of coherence can be enhanced through various therapeutic approaches. Compassion-focused therapy is an effective approach to enhancing self-compassion and personal agency among university students, as well as to improving psychological well-being [13].…”
Section: Discussionsupporting
confidence: 84%
“…The current study concluded that compassion-focused therapy is effective in improving feelings of coherence, as supported by other studies [22], [31], [39], which indicated that the sense of coherence can be enhanced through various therapeutic approaches. Compassion-focused therapy is an effective approach to enhancing self-compassion and personal agency among university students, as well as to improving psychological well-being [13].…”
Section: Discussionsupporting
confidence: 84%
“…These activities are intended to improve and enhance the quality of care for people with dementia ( 48 ). In another study, researchers in Taiwan demonstrated a beneficial effect of horticultural therapy applied for 12 weeks but in people without dementia requiring long-term care on SOC levels ( 49 ). The positive role of SOC in health promotion is also emphasized by other authors, while postulating the need for further research ( 10 , 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Eighteen studies were included in this review. These studies were conducted in Norway (n = 4) (Bragstad et al, 2020;Bringsvor et al, 2018;Langeland et al, 2019;Sundsli et al, 2014), China (n = 2) (Jueng & Chen, 2022;Lei, 2019), Iran (n = 2) (Hourzad et al, 2018;Musavinasab et al, 2016), Singapore (n = 2) (Seah et al, 2022;Tan et al, 2016), Sweden (n = 2) (Arola et al, 2018;Malm et al, 2018), Denmark (n = 1) (Jensen et al, 2016), Finland (n = 1) (Hemberg ADDQoL; DDS 1. The experimental group had a significantly greater improvement in overall situation of SOC, comprehensibility from T0 (baseline) to T1 (1 week after completion of the project) as compared with the control group.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…Intervention frequency in most studies (n = 6) was once a week (Arola et al, 2018;Bringsvor et al, 2018;Jueng & Chen, 2022;Lei, 2019;Seah et al, 2022;von Humboldt & Leal, 2013), while six studies did not describe their intervention frequency (Hemberg et al, 2022;Hourzad et al, 2018;Krug et al, 2021;Malm et al, 2018;Musavinasab et al, 2016;Sundsli et al, 2014).…”
Section: Intervention Length Duration Of Each Time and Frequencymentioning
confidence: 99%